2018
DOI: 10.1155/2018/7475626
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor-γPrevents Cholesterol Gallstone Formation in C57bl Mice by Regulating Bile Acid Synthesis and Enterohepatic Circulation

Abstract: To investigate the role of the peroxisome proliferator-activated receptor-γ (PPARγ) in the progression of cholesterol gallstone disease (CGD), C57bl/6J mice were randomized to the following groups (n=7/group): L (lithogenic diet, LGD), LM (LGD+pioglitazone), CM (chow diet+pioglitazone), and NC (normal control, chow diet). Gallbladder stones were observed by microscopy. Histological gallbladder changes were assessed. Bile acids (BA) and cholesterol were measured in the serum, bile, and feces. Proteins and mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Our results showed that the LD-fed guinea pigs had a 85.7% gallstone formation rate. The present data also further confirmed the preventive effects of pioglitazone on the CGD in the model of guinea pigs as shown in the mouse model [24]. As a key protein controlling intestinal cholesterol absorption, NPC1L1 was expressed by enterocytes, identified as a target of ezetimibe [25].…”
Section: Discussionsupporting
confidence: 85%
“…Our results showed that the LD-fed guinea pigs had a 85.7% gallstone formation rate. The present data also further confirmed the preventive effects of pioglitazone on the CGD in the model of guinea pigs as shown in the mouse model [24]. As a key protein controlling intestinal cholesterol absorption, NPC1L1 was expressed by enterocytes, identified as a target of ezetimibe [25].…”
Section: Discussionsupporting
confidence: 85%
“…A stable enterohepatic circulation may prevent cholesterol gallstone formation. [18] Based on the above, we speculated that the formation of gallstones was closely correlated with NTCP deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our research showed that SCFAs were present at lower levels in AD + HFD mice. The depletion of butyrate-producing microbes by antibiotic treatment reduced epithelial signaling through the intracellular butyrate sensor PPARγ (Byndloss et al, 2017 ), which induced expression of genes involved in enterohepatic circulation and bile acid synthesis (Wang et al, 2018 ). As signaling molecules, SCFAs could adjust lipogenesis, gluconeogenesis and cholesterol synthesis notably through the G-protein coupled receptors GPR43/FFAR2 and GPR41/FFAR3 (Schoeler and Caesar, 2019 ).…”
Section: Discussionmentioning
confidence: 99%